2017
DOI: 10.1016/j.csm.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Female Athlete Triad

Abstract: Synopsis Despite over three decades of research on the Female Athlete Triad, research gaps remain. Although low energy availability (EA) is the key etiological factor in the Triad and the pathways to low EA are varied, its effects can be modified by several factors. As such, a more individualized approach to identifying and treating low EA is warranted. Accurate screening, diagnosis, and treatment of disordered eating (DE) remains a challenge, however, recent techniques combined with novel educational and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 118 publications
0
12
0
1
Order By: Relevance
“…A large volume of work spanning nearly three decades has identified the Female Athlete Triad, a syndrome consisting of disordered eating, amenorrhea, and osteoporosis (Yeager et al, 1993;Otis et al, 1997;Ranson et al, 2018). Although these three signs tend to be the most commonly thought of, the triad syndrome has been updated to include broader conditions: low energy availability (with or without disordered eating), menstrual dysfunction, and low bone mineral density (Nattiv et al, 2007;Williams et al, 2017). Recently, a parallel to the Female Athlete Triad has been proposed for male athletes that comprises hypogonadotropic hypogonadism, low energy availability, and low mineral bone density (Tenforde et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large volume of work spanning nearly three decades has identified the Female Athlete Triad, a syndrome consisting of disordered eating, amenorrhea, and osteoporosis (Yeager et al, 1993;Otis et al, 1997;Ranson et al, 2018). Although these three signs tend to be the most commonly thought of, the triad syndrome has been updated to include broader conditions: low energy availability (with or without disordered eating), menstrual dysfunction, and low bone mineral density (Nattiv et al, 2007;Williams et al, 2017). Recently, a parallel to the Female Athlete Triad has been proposed for male athletes that comprises hypogonadotropic hypogonadism, low energy availability, and low mineral bone density (Tenforde et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the male triad appear to be less frequent, less severe, and more treatable than the female triad ( De Souza et al, 2019 ). Central to the athlete triad of both men and women is low energy availability, which is frequently exacerbated by disordered eating ( Williams et al, 2017 ). For both men and women, the etiology of the triad is similar: pressure to enhance performance or maintain an advantageous aesthetic can lead to an athlete expending excessive energy in their exercise and consuming insufficient nutrients to maintain homeostasis ( Torstveit et al, 2008 ; Sundgot-Borgen and Torstveit, 2010 ; Ranson et al, 2018 ; De Souza et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, younger athletes reported higher rates of menstrual dysfunction than older athletes, which contradicts the findings of Torstveit and Sundgot-Borgen [ 8 ], who found no difference in menstrual dysfunction prevalence in athletes or controls divided into three age groups (16–19, 20–29, and 30–39 years). However, it has been suggested that the risk of menstrual dysfunction decreases with advanced gynecological age (chronological age minus age at menarche) [ 35 ], which might explain our findings.…”
Section: Discussionmentioning
confidence: 54%
“…Table 4. The number of examinees in groups with BMI<18,5 kg/m 2 deficiency or of eating disorders, ranging from 7.1% to unbelievable 89.2% depending on a sport (Williams, Statuta and Austin, 2017). Diagnostic screening tests, suggested to be used in primary health care, are of great value and we used them as well.…”
Section: Resultsmentioning
confidence: 99%